Radionuclide-Based Cancer Imaging Targeting the Carcinoembryonic Antigen - Hao Hong (Biomarker Insights, 2008)
Carcinoembryonic antigen (CEA), highly expressed in many cancer types, is an important target for cancer diagnosis and therapy. Radionuclide-based imaging techniques (gamma camera, single photon emission computed tomography [SPECT] and positron emission tomography [PET]) have been extensively explored for CEA-targeted cancer imaging both preclinically and clinically. Briefly, these studies can be divided into three major categories: antibody-based, antibody fragment-based and pretargeted imaging. Radiolabeled anti-CEA antibodies, reported the earliest among the three categories, typically gave suboptimal tumor contrast due to the prolonged circulation life time of intact antibodies. Subsequently, a number of engineered anti-CEA antibody fragments (e.g. Fab’, scFv, minibody, diabody and scFv-Fc) have been labeled with a variety of radioisotopes for CEA imaging, many of which have entered clinical investigation. CEA-Scan (a 99m Tc-labeled anti-CEA Fab’ fragment) has already been approved by the United States Food and Drug Administration for cancer imaging. Meanwhile, pre-targeting strategies have also been developed for CEA imaging which can give much better tumor contrast than the other two methods, if the system is designed properly. In this review article, we will summarize the current state-of-the-art of radionuclide-based cancer imaging targeting CEA. Generally, isotopes with short half-lives (e.g. 18 F and 99m Tc) are more suitable for labeling small engineered antibody fragments while the isotopes with longer half-lives (e.g. 123 I and 111 In) are needed for antibody labeling to match its relatively long circulation half-life. With further improvement in tumor targeting efficacy and radiolabeling strategies, novel CEA-targeted agents may play an important role in cancer patient management, paving the way to “personalized medicine”.